The Uniqueness of Changes: Characteristics and Applications - Ray, Baishakhi; Nagappan, Meiyappan; Bird, Christian; Zimmermann, Tom; Nagappan, Nachi (Microsoft, 2014)
Changes in software development come in many forms. Some changes are frequent, idiomatic, or repetitive (e.g. adding checks for nulls or logging important values) while others are unique. We hypothesize that unique changes are different from the more common similar (or non-unique) changes in important ways; they may require more expertise or represent code that is more complex or prone to mistakes. As such, these changes are worthy of study. In this paper, we present a definition of unique changes and provide a method for identifying them in software project history. Based on the results of applying our technique on the Linux kernel and two large projects at Microsoft, we present an empirical study of unique changes. We explore how prevalent unique changes are and characterize where they occur along the architecture of the project. We further investigate developers' contribution towards uniqueness of changes. We also describe potential applications of leveraging the uniqueness of change and implement two such applications, evaluating the risk of changes based on uniqueness and providing change recommendations for non-unique changes.